Anisotropic loss of toughness with physical aging of work toughened polycarbonate. Issue 4 (12th June 2013) - Strabala, Kyle; Meagher, Shawn; Landais, Charles; Delbreilh, Laurent; Negahban, Mehrdad; Saiter, Jean‐Marc; Turner, Joseph; Ingram, Adam; Golovchak, Roman
<x xml:space="preserve">Abstract</x> We have studied the response of mechanically toughened and physically aged polycarbonate primarily using Charpy impact and ultrasonic wave speed measurements. The toughening was conducted through plastic compression on as‐received PC. The Charpy impact tests showed anisotropic toughening, both in the absorbed energy and in the mode of fracture. The amount of toughening with plastic compression, even though anisotropic, is centered around the response of annealed and quenched samples, which represent the response of an unaged PC. There was an anisotropic drop in the toughness of some samples with aging. The time of this drop was uncorrelated in the different directions and disappeared for the highly toughened samples. This transition was bimodal and statistically distributed between either a fully ductile or a fully brittle failure. As the samples were prepared in a manner to remove induced residual stresses, this drop in toughening may be associated with an intrinsic anisotropic thermal aging of the deformed material. POLYM. ENG. SCI., 54:794–804, 2014. © 2013 Society of Plastics Engineers